인체지방유래 간질세포의 부착 및 연골분화유도를 위한 PLGA 지지체의 플라즈마 처리 효과 - 동춘희; 전영준; 조현미; 오득영; 한동근; 이종원; 안상태 (대한성형외과학회, 2006)
High-density micromass culture was needed to take three dimensions culture with ASCs(adipose derived stromal cells) and chondrogenesis. However, the synthetic polymer has hydrophobic character and low affinity to cells and other biomolecules. Therefore, the surface modification without changes of physical and chemical properties is necessary for more suitable condition to cells and biomolecules. This study was performed to investigate the effect of surface modification of poly (lactic-co-glycolic acid)(PLGA) scaffold by plasma treatment (P(+)) on the adhesion, proliferation and chondrogenesis of ASCs, and not plasma treatment (P(-)). ASCs were isolated from human subcutaneous adipose tissue obtained by lipectomy and liposuction. At 1 hour 30 minutes and 3days after cell seeding onto the P(-) group and the P(+) group, total DNA amount of attached and proliferated ASCs markedly increased in the P(+) group (p<0.05). The changes of the actin under confocal microscope were done for evaluation of cellular affinity, at 1 hour 30 minutes, the shape of the cells was spherical form in all group. At 3rd day, the shape of the cells was fiber network form and finely arranged in P(+) group rather than in P(-) group. RT-PCR analysis of cartilage- specific type II collagen and link protein were expressed in 1, 2 weeks of induction. Amount of Glycoaminoglycan (GAG) markedly increased in P(+) group(p<0.05). In a week, extracellular matrix was not observed in the Alcian blue and Safranin O staining. However in 2 weeks, it was observed that sulfated proteoglycan increased in P(+) group rather than in P(-) group.In conclusion, we recognized that plasma treatment of PLGA scaffold could increase the hydrophilic property of cells, and provide suitable environment for high-density micromass culture to chondrogenesis